2005
DOI: 10.1523/jneurosci.3831-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cyclin-Dependent Kinase 5 Activation by Amyloid Precursor Protein: A Novel Excitoprotective Mechanism Involving Modulation of Tau Phosphorylation

Abstract: Alzheimer's disease is cytopathologically characterized by loss of synapses and neurons, neuritic amyloid plaques consisting of ␤-amyloid (A␤) peptides, and neurofibrillary tangles consisting of hyperphosphorylated tau protein in susceptible brain regions. A␤, which triggers a cascade of pathogenic events including tau phosphorylation and neuronal excitotoxicity, is proteolytically derived from ␤-amyloid precursor protein (APP); the pathological and physiological functions of APP, however, remain undefined. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 71 publications
9
67
0
Order By: Relevance
“…In addition to a possible direct influence on CDK5 activation, ATRA may inhibit CDK5 through stabilizing APP. Because APP has been shown to reciprocally regulate CDK5 activity (Han et al, 2005), ATRA-induced inhibition of APP processing observed in APP/PS1 mice may cause an enhanced stability of APP, thereby resulting in indirect inhibition of CDK5 activity and attenuation of tau phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a possible direct influence on CDK5 activation, ATRA may inhibit CDK5 through stabilizing APP. Because APP has been shown to reciprocally regulate CDK5 activity (Han et al, 2005), ATRA-induced inhibition of APP processing observed in APP/PS1 mice may cause an enhanced stability of APP, thereby resulting in indirect inhibition of CDK5 activity and attenuation of tau phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study by Han et al demonstrated that defects in neurite outgrowth and branching seen in the primary neuronal cultures isolated from APP knockout (APP KO) mice were restored by sAPPα (Han et al, 2005). This neurotrophic effect of sAPPα was suggested to be due to its inhibitory effect on cyclin-dependent kinase 5 (CDK5), as addition of the CDK5 inhibitor roscovitine was reported to increase neuritic outgrowth on glutamate-treated primary neuronal cultures from APP KO mice (Han et al, 2005). While there is no direct evidence linking the effects of sAPPα on CDK5 to neuronal hypertrophy, they may be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days, cells were infected independently or co-infected with empty vector (EV), the constructs of p5, p25, p35, wild-type Cdk5, and dominant negative Cdk5 (changing Lys 33 to Thr 33 ) using the adenoviral vector (pAdTrack-CMV) packaging system as described above. After 48 h, cells were treated with roscovitine (20 M) for 1 h and/or for 6 h with 10 M A␤(1-42) (incubated at 37°C for 7 days before use).…”
Section: Methodsmentioning
confidence: 99%
“…It reduces Tau hyperphosphorylation and protects transfected HEK cells and neurons from apoptosis induced by Cdk5-p25 (23,27,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). To produce a smaller and more effective inhibitory peptide of Cdk5-p25 for potential therapeutic use, we designed and constructed five short peptides in GST vectors, as shown in Fig.…”
Section: Identification Of Cdk5-inhibitory Peptides Derived From P35-mentioning
confidence: 99%